2019
DOI: 10.12659/msm.914860
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Reverse Diabetic Nephropathy Disease via Lipoxin A4 by Targeting Transforming Growth Factor β (TGF-β)/smad Pathway and Pro-Inflammatory Cytokines

Abstract: Background Diabetic nephropathy (DN) is the leading cause of end-stage renal disease. Mesenchymal stem cells (MSCs) treatment has been proved to be effective in DN models by protecting renal function and preventing fibrosis. However, the underlying mechanism is unclear. Previous research indicated diabetes and associated complications may be attributed to failed resolution of inflammation, which is deliberately regulated by pro-resolving lipids, including lipoxins (LXs), resolvins (Rv) D and E ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…These activities of LXA 4 are regulated by the G protein-coupled ALX/FPR2 receptor 18,19 . LXA4 reportedly reduces DM-related renal fibrosis by targeting TGF-β/Smad signaling and suppresses liver fibrosis in experimental models by regulating the immune responses and modulating the expression of regeneration genes 20,21 . It also lowers TGF-β levels in bleomycin-induced pulmonary fibrosis and exhibits an anti-fibrotic effect 22 .…”
Section: Introductionmentioning
confidence: 99%
“…These activities of LXA 4 are regulated by the G protein-coupled ALX/FPR2 receptor 18,19 . LXA4 reportedly reduces DM-related renal fibrosis by targeting TGF-β/Smad signaling and suppresses liver fibrosis in experimental models by regulating the immune responses and modulating the expression of regeneration genes 20,21 . It also lowers TGF-β levels in bleomycin-induced pulmonary fibrosis and exhibits an anti-fibrotic effect 22 .…”
Section: Introductionmentioning
confidence: 99%
“…week observation, the mortality in the MSCs-treated group (75.0%, 9/12) was lower than that in the DNgroup (33.3%, 4/12) [28]. Similarly, Xian et al found 2 deaths in the hUCB-MSCs group, which was obviously less than the T1DM group (6 deaths) at the end of the study [29].…”
Section: Search Resultsmentioning
confidence: 88%
“…The in ltration of renal macrophages and the expression of in ammatory cytokines were effectively inhibited by early intervention of MSCs in DM rats through the immune regulation and paracrine secretion of renal protective factors, restoring the homeostasis of immune microenvironment [27]. The failure of in ammatory regression may matter DM and its complications, and BM-MSCs could block the exacerbation of DKD through the LXA4-ALX/FPR2 axis to inhibit glomerulosclerosis and secretion of proin ammatory cytokines [28].…”
Section: Anti-in Ammationmentioning
confidence: 99%
“…In 2014, another study highlighted the importance of the enhancement of CD206‐positive M2 macrophage infiltration in the protection of AKI mice from extreme tubular lesions upon MSCs injection (Yanqiu Geng et al, 2014). Bai et al exhibited that MSCs administration decreased diabetic nephropathy (DN) profession by LXA4‐ALX/FPR2 axis and suppressed kidney fibrosis through targeting TGF‐β/Smad pathway and inhibition of TNF‐ α, IL‐6, IL‐8, and IFN‐γ expression in DN rats (Bai et al, 2019). Recently, it has been suggested that downregulation of poly (ADP‐ribose) polymerase 1, acting as caspase activator, accompanied with the suppressing of the expression of p57 cell cycle inhibitory protein ameliorate chronic kidney failure following MSCs infusion (Cetinkaya, Unek, Kipmen‐Korgun, Koksoy, & Korgun, 2019).…”
Section: Mscs In Regenerative Medicinementioning
confidence: 99%